Pengaruh Pemberian Ekstrak Daun Mahkota Dewa(Phaleria Macrocarpa) pada Gambaran Histopatologi Paru Tikus Putih (Rattus Norvegicus) Galur Wistar yang Dipapar Asap Rokok - NGURAH BAGUS RADITYA SRI DAMAR; EDIJONO; JANTO POERNOMO HADI; TROEF SOEMARNO (Universitas Hang Tuah, 2019)
ABSTRACT Background Smoking and getting exposed to cigarette smoke in a long period of time can cause inflammatory response on respiratory tract. Mahkota dewa leaf contains beneficial biological component, such as flavonoid, alkaloid, and saponin that have anti-inflammatory, anti-cancer, and many others. Aim : to determine the effect of administration of mahkota dewa leaf (Phaleria macrocarpa) extract of inflamatory cells on lung histopathology in white male Wistar rats (Rattus norvegicus) exposed to cigarette smoke. Methods : experimental research using Post-Test Only Control Group Design. The subject in this research were 30 male Wistar Rats (Rattus norvegicus) which were divided into 4 groups, a group without given any treatment (K-), a group where they only getting exposed to cigarette smoke (K+), a group where they exposed to cigarette smoke and given mahkota dewa leaf extract at 1500 mg/kgBW/day dose (K1), and the group exposed to cigarette smoke and a mahkota dewa leaf extract at a 2500 mg/kgBW/day dose (K2). , then the rats sacrificed to be made lung histological preparats to count the number of inflamatory cells Result : There was a significant difference on lung histopathology between K- and K+, P1, and P2. There was no significant difference infiltration cells on lung histopathology between K+, K1 and K2. Conclusion : Exposure to 5 cigarette smoke in 21 days caused lung histopathology changes. However, there was no effect of the administration of mahkota dewa leaves extract at 1500 mg/kgBW/day and 2500 mg/kgBW/day on lung histopathology of white male Wistar rats exposed to 5 cigarette smoke in 21 days